PERAN PEMERINTAH ACEH BESAR DALAM PENCEGAHAN GENERASI STUNTING DI KECAMATAN PULO ACEH KABUPATEN ACEH BESAR - Fikri (Journal of Research and Development on Public Policy, 2022)
Stunting which is a condition coinic malnutrision since 1000 day of a child’s lif is still a health problem in indonesia, ranking second in the word. The couses of stunting include poor parenting, inadequate care, barriers to access to nutrition and clean water. As well as infectious diseases. Stunting prevention Plays an importaint rolle intackling the causes of stunting from its roots. One of them is by providing education to cadres about stunting pevention. Training provided to cadres can improve public health from the dissemination of health information. This research want to see how effective stunting education is in increasing cadre knowledge about stunting prevention. This study used a Systematic Literature Review by Systematically Searching for studies using the PRISMA protocol on ten national article portal. Two article were selected to be the main discussion of the research, all of which were studies with a cross- sectional design, with stunting prevention education for cadres. The greatest effectiveness in increasing the knowledge of cadres is through audiovisul media and lecture and discussion methods, namely as much as 70%.